Shallow Geothermal Energy Systems: Investigating possible viable solutions in the building sector - Aresti, Lazaros (My University, 2020)
This thesis provides a holistic study on Shallow Geothermal Energy Systems, which includes an economic evaluation, a parametric analysis of the effect of groundwater, the use of buildings’ foundations and a Life Cycle Analysis (LCA) with regard to the environmental impact of Ground Source Heat Pumps (GSHPs). The outcome is a contribution toward shedding light or finding the way to use more extensively Shallow Geothermal Energy as an attractive Renewable Energy Source (RES) for heating and cooling residential buildings.
Keywords: Geothermal Energy Systems